Evaluation of degree of conversion and hardness of dental composites photoactivated with different light guide tips - Galvão, Marília Regalado [UNESP]; Caldas, Sergei Godeiro Fernandes Rabelo [UNESP]; Bagnato, Vanderlei Salvador; Rastelli, Alessandra Nara de Souza [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (My University, 2013)
Objective: The aim of this study was to evaluate the degree of conversion and hardness of different composite resins, photo-activated for 40 s with two different light guide tips, fiber optic and polymer. Methods: Five specimens were made for each group evaluated. The percentage of unreacted carbon double bonds (% C=C) was determined from the ratio of absorbance intensities of aliphatic C=C (peak at 1637 cm-1) against internal standard before and after curing of the specimen: aromatic C-C (peak at 1610 cm-1. The Vickers hardness measurements were performed in a universal testing machine. A 50 gf load was used and the indenter with a dwell time of 30 seconds. The degree of conversion and hardness mean values were analyzed separately by ANOVA and Tukey's test, with a significance level set at 5%. Results: The mean values of degree of conversion for the polymer and fiber optic light guide tip were statistically different (P<.001). The hardness mean values were statistically different among the light guide tips (P<.001), but also there was difference between top and bottom surfaces (P<.001). Conclusions: The results showed that the resins photo-activated with the fiber optic light guide tip promoted higher values for degree of conversion and hardness.
Keywords: Composite resins; Hardness; Polymerization